Table of Content - - (Journal of Islamic Sciences, 2024)
Table of Content:1. Achieving a chapter (prayer conditions) in the Sunni talents book explanation of the urban introduction of Sheikh Said BaishenMr. Mohammed Jamal Mohammed Al-Sagaf2. Meanings of victory in the Holy Qur’an and its causesMr. Ibrahim Hammad Yousef Odeh
Keywords: Journal of Islamic Sciences